2013
DOI: 10.1177/0300985813509388
|View full text |Cite
|
Sign up to set email alerts
|

Canine Mammary Tumors

Abstract: Although there have been several studies on the use of immunohistochemical biomarkers of canine mammary tumors (CMTs), the results are difficult to compare. This article provides guidelines on the most useful immunohistochemical markers to standardize their use and understand how outcomes are measured, thus ensuring reproducibility of results. We have reviewed the biomarkers of canine mammary epithelial and myoepithelial cells and identified those biomarkers that are most useful and those biomarkers for invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(59 citation statements)
references
References 127 publications
2
48
0
8
Order By: Relevance
“…Similar to us, the co-expression of PDPN in CAFs with HER2 receptor expression has also been demonstrated in cancer cells in IDC in women (15). HER2 is an important marker used in the diagnosis of breast cancer in women, while it is more and more frequently used for IHC tests in veterinary medicine (9)(10)(11). This receptor participates in the oncogenesis processes, by affecting cancer cell migration, increasing angiogenesis, and metastasis of cancer cells (9)(10)(11)44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to us, the co-expression of PDPN in CAFs with HER2 receptor expression has also been demonstrated in cancer cells in IDC in women (15). HER2 is an important marker used in the diagnosis of breast cancer in women, while it is more and more frequently used for IHC tests in veterinary medicine (9)(10)(11). This receptor participates in the oncogenesis processes, by affecting cancer cell migration, increasing angiogenesis, and metastasis of cancer cells (9)(10)(11)44).…”
Section: Discussionmentioning
confidence: 99%
“…HER2 is an important marker used in the diagnosis of breast cancer in women, while it is more and more frequently used for IHC tests in veterinary medicine (9)(10)(11). This receptor participates in the oncogenesis processes, by affecting cancer cell migration, increasing angiogenesis, and metastasis of cancer cells (9)(10)(11)44). In these published studies, there is no relationship reported between the intensity of the HER2 receptor expression and the level of PDPN expression in CAFs in mammary tumours in bitches.…”
Section: Discussionmentioning
confidence: 99%
“…The primary canine mammary tumor, the cell line and xenotransplanted tumors were considered positive for AE1/AE3, CK-14, p63, vimentin, actin, E-Cad and COX-2 when more than 10% of the neoplastic cells were positive [ 21 ]. Beside this, IPC-366 phenotype markers were scored in pellet sections by a computer assisted image analyzer (image J), counting up to 1000 cells.…”
Section: Methodsmentioning
confidence: 99%
“…Diagnosis and staging of these tumors is currently achieved by using a combination of pathology and physical diagnosis [15], although attempts have been made to apply immunohistochemical analysis to this problem, which can be challenging due to extended/variable fixation and sectioning artifacts and the requirement for specific target labeling [162225]. As a result, diagnosis and staging of canine mammary tumors is still largely based on standard traditional pathological analysis.…”
Section: Introductionmentioning
confidence: 99%